Assessing gage: an online tool for improving gender visibility in STEMM - Elizabeth A. McCullagh; Francesca Bernardi; Monica Malta; Katarzyna Nowak; Alison R. Marklein; Katie Van Horne; Tiffany Lee Clark; Susan J. Cheng; Maryam Zaringhalam; Lauren L. Edwards (Canadian Science Publishing, 2021)
Women continue to be underrepresented and less visible in the fields of science, technology, engineering, mathematics, and medicine (STEMM). 500 Women Scientists created and launched in January 2018 a global (>140 countries to date), online, open-access directory of women in STEMM fields. This directory-recently renamed gage-now also includes gender diverse persons (i.e., additional underrepresented genders) in STEMM fields. The purpose of the directory is to make these scientists' expertise easier to locate and access for conference organizers, journalists, policy makers, educators, and others. Here, we undertake an assessment of the directory using surveys, Google Analytics, and focus groups to understand its efficacy and direction to date and identify future improvements we pledge to undertake. Through this assessment-conducted externally and in accordance with privacy protocols by Concolor Research-we identified who and how people are using our directory, why people signed up to be a resource, and areas for improvement. Through such assessment, we can learn how to enhance the directory's efficacy and our broader efforts to boost the visibility of underrepresented people in STEMM.